Perception of dental practitioners in and around Kanpur city towards forensic odontology: a cross sectional study - Mehrotra, Vishal; Mishra, Gauri; Sachdev, Rohan; Garg, Kriti; Mukherjee, Sekhar; Saxena, Shubhra (International Journal of Research in Medical Sciences, 2019)
Background: In the present era, forensic odontology has expanded as one of the most remarkable and commendable branches of Forensic Sciences. Through forensic odontology, a dentist plays a very important role in crime investigation of any type. The main objective of the present study was to evaluate the knowledge, percipience and practical perception of forensic odontology among the dental practitioners in and around Kanpur city. Methods: A cross-sectional study was conducted from Jan-Mar 2019 among 207 dental practitioners in and around Kanpur city including 143 BDS and 64 MDS through a questionnaire proforma. The proforma consisted of 20 questions prepared on the topic of forensic Odontology and role of dentist in the field of forensic Odontology. Results: In this study, nearly 70% of dental practitioners were aware of the role of dentist in forensics, and around 60% of dental practitioners maintain dental records with recording of personal data and clinical findings being the most frequently used method. In the present study most of the dental practitioners were not aware of significance of chelioscopy (63%) and rugoscopy (66%) in field of forensic Odontology. Nearly 70% of dentist accepted the fact that their level of knowledge regarding forensic dentistry is inadequate and nearly 40% of them were not confident in giving any opinion regarding the same. Conclusions: This study shows that although there is an adequate awareness of role of dentist in forensic Odontology, but there is lack of good knowledge, confidence and practical approach of the dental practitioners towards forensic Odontology which may be due to lack of training, experience, exposure in field of forensics. Thus, the need of the hour lies in updating the knowledge and also developing interest of the dental practitioners regarding forensic Odontology.